The Effect of Sensory Disturbance and Cognitive Load on the Transition of Relative Phase in Bimanual Coordination Task in Elderly Women - Alireza Farsi; sana Soltani; Elham Mahdipour (Vesnu Publications, 2016)
Introduction: Bimanual coordination is an important ability that is used in many daily tasks including throwing, catching and many sport skills. Performing these activities depends on many factors such as sensory and attentional features. The purpose of this study was to investigate the effect of sensory disturbance and cognitive load on time of the relative phase transition in anti-phase bimanual coordination pattern among elderly women. Materials and Methods: Twelve right-handed healthy old women (66.0 ± 2.8 years old) of the twenty four voluntaries were selected based on the inclusion criteria in this study. Participants started their movement on bimanual coordination device with anti-phase pattern at the frequency of 0.50 Hz .Then, after each five seconds, 0.25 Hz was gradually increased to frequency and continued until the anti-phase pattern turned to in-phase pattern. This task was performed in two different conditions concluding with cognitive load and without it with the disturbance of visual, auditory and proprioceptive senses. Data were analyzed using 2 × 4 repeated-measures analysis of variences, Bonferroni correction and paired-samples t tests. Results: The main effects of cognitive load (P = 0.004), sensory disturbance (P = 0.040) and interaction (P = 0.020) were mainly significant. The effect of sensory disturbance in the condition of without cognitive load was significant (P = 0.004). In the condition of without cognitive load, proprioceptive disturbance significantly affected the time of the relative phase transition. Conclusion: Results indicated the prominent role of cognitive load on selected task. In the condition of without cognitive load, ‎proprioceptive sense had a stronger effect than visual and auditory senses; but in the presence of cognitive load, the ‎effect of sensory disturbance was lost. In terms of change in time of transition of relative phase with change in task ‎and environmental constraints, results of this study are in line with dynamic systems view.‎